Probing tumor microenvironment in patients with newly diagnosed glioblastoma during chemoradiation and adjuvant temozolomide with functional MRI. Issue 1 (December 2018) - Ina Ly, K.; Vakulenko-Lagun, Bella; Emblem, Kyrre; Ou, Yangming; Da, Xiao; Betensky, Rebecca; Kalpathy-Cramer, Jayashree; Duda, Dan; Jain, Rakesh; Chi, Andrew; Plotkin, Scott; Batchelor, Tracy; et al.
Abstract Functional MRI may identify critical windows of opportunity for drug delivery and distinguish between early treatment responders and non-responders. Using diffusion-weighted, dynamic contrast-enhanced, and dynamic susceptibility contrast MRI, as well as pro-angiogenic and pro-inflammatory blood markers, we prospectively studied the physiologic tumor-related changes in fourteen newly diagnosed glioblastoma patients during standard therapy. 153 MRI scans and blood collection were performed before chemoradiation (baseline), weekly during chemoradiation (week 1–6), monthly before each cycle of adjuvant temozolomide (pre-C1-C6), and after cycle 6. The apparent diffusion coefficient, volume transfer coefficient (Ktrans ), and relative cerebral blood volume (rCBV) and flow (rCBF) were calculated within the tumor and edema regions and compared to baseline. Cox regression analysis was used to assess the effect of clinical variables, imaging, and blood markers on progression-free (PFS) and overall survival (OS). After controlling for additional covariates, high baseline rCBV and rCBF within the edema region were associated with worse PFS (microvessel rCBF: HR = 7.849, p  = 0.044; panvessel rCBV: HR = 3.763, p  = 0.032; panvessel rCBF: HR = 3.984;p  = 0.049). The same applied to high week 5 and pre-C1 Ktrans within the tumor region (week 5 Ktrans : HR = 1.038, p  = 0.003; pre-C1 Ktrans : HR = 1.029, p  = 0.004). Elevated week 6 VEGF levels were associated with worse OS (HR = 1.034;p  = 0.004). Our findings suggest a role for rCBV and rCBF at baseline and Ktrans and VEGF levels during treatment as markers of response. Functional imaging changes can differ substantially between tumor and edema regions, highlighting the variable biologic and vascular state of tumor microenvironment during therapy.